Pengaruh Temperatur Reaktor Terhadap Viskositas Bahan Bakar Cair Hasil Proses Pirolisis Sampah Plastik Polypropylene - Muqsith, Muchammad Aufa; Suarnadwipa,, I Nengah; Adnyana, I Wayan Bandem (Teknik Desain Mekanika; Vol 13 No 3 (2024): Juli 2024 : Teknik Desain Mekanika, 2024)
Abstract The increasing population in Indonesia has resulted in energy needs continuing to rise, and one of the largest contributors to energy consumption is fuel oil. On the other hand, an increasing population also results in higher volumes of waste being produced, and one of the largest contributors to waste is polypropylene (PP) plastic waste. In an effort to meet energy needs and reduce the volume of plastic waste, this can be done through the pyrolysis method. The main product of plastic pyrolysis is liquid fuel, and to find out whether the liquid fuel product is suitable for use as an alternative fuel, one must know the viscosity value. So, the aim of this research is to find out how temperature variations in the pyrolysis reactor affect the viscosity of liquid fuel produced from polypropylene plastic pyrolysis. The temperature variations in the reactor in this study were 300 oC, 325 oC, 350 oC, 375 oC and 400 oC. The material used was 1 kg of polypropylene plastic waste at each temperature variation. The highest viscosity results were at a reactor temperature variation of 400 oC with a value of 0.819 cP, while at a reactor temperature variation of 300 oC, the viscosity was only 0.671 cP. Based on the results of this research, the temperature in the reactor influences the viscosity of the liquid fuel produced. Keywords: Pyrolysis, Polypropylene (PP), Temperature, Liquid Fuel, Viscosity